THE INFLUENCE OF CUSTOMER EXPERIENCE, USER EXPERIENCE, AND SWITCHING BARRIER ON PURCHASE INTEREST IN THE SHOPEEFOOD APPLICATION IN SOUTH JAKARTA - An Nida Rofiqoh Amsari; Suadi Sapta Putra; Kumba Digdowiseiso (SEAN Institute, 2023)
This research aims to determine the influence of the relationship between customer experience, user experience and switching barrier variables on purchasing interest in shoppefood applications in South Jakarta. This research is a quantitative descriptive analysis research. The data source for this research uses primary data in the form of a questionnaire. This research data was given to 100 respondents aged 15-55 years and who have used the ShopeeFood application at least once who live in South Jakarta. In taking samples for this research, a purposive sampling technique was used. The data analysis technique used is multiple linear regression and hypothesis testing using t-statistics processed in SPSS 25 to test the regression coefficient. Of the 100 research subjects, most of the research subjects were dominated by women (79%) and most of their jobs were students (79%). There is a significant relationship between the customer experience variable and purchase intention with the calculated t value (8.924) being greater than the t table (1.984). There is no relationship between the user experience variable and purchasing interest with a calculated t value (-0.524) which is smaller than the t table (1.984) and the switching barrier variable with purchasing interest with a calculated t value (0.792) which is smaller than the t table (1.984). Based on partial research results, it can be concluded that customer experience has a positive and significant effect on purchasing interest. However, there is no relationship between user experience and switching barriers on purchasing interest.